Multiple Levels of Chemokine Receptor Regulation in the Control of Mouse Natural Killer Cell Development - Bernardini, Giovanni; Benigni, Giorgia; Antonangeli, Fabrizio; Ponzetta, Andrea; Santoni, Angela (Frontiers in Immunology, 2014)
Chemokines play a fundamental role in lymphocyte development, mainly attributable to the control of the correct localization in the proper microenvironments of cells undergoing maturation. NK cell development occurs in the bone marrow where their localization is regulated by the balance of chemokine function in cell retention into tissues and mobilization into circulation. In addition, NK cells from several extra-medullary tissues are phenotypically and functionally different from their circulating counterpart suggesting that maturation can be completed in organs other than BM. Indeed, a role of chemokines in NK cell localization into tissues during homeostatic conditions is also documented. In this review we summarize the current notion related to the relevance of several chemokine/chemokine receptor axes in NK cell development with a focus on the regulation of their expression and function.